2019
DOI: 10.1021/acsnano.9b07277
|View full text |Cite
|
Sign up to set email alerts
|

Translucency of Graphene to van der Waals Forces Applies to Atoms/Molecules with Different Polar Character

Abstract: Graphene has been proposed to be either fully transparent to van der Waals interactions to the extent of allowing to switch between hydrophobic and hydrophilic behaviour, or partially transparent (translucent), yet there has been considerable debate on this topic, which is still ongoing. In a combined experimental and theoretical study we investigate the effects of different metal substrates on the adsorption energy of atomic (argon) and molecular (carbon monoxide) adsorbates on high-quality epitaxial graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In addition to wetting transparency, other surface-related properties might also be transparent to 2D materials. Adsorption transparency, which has implications in catalysis, was recently reported and warrants additional attention. …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to wetting transparency, other surface-related properties might also be transparent to 2D materials. Adsorption transparency, which has implications in catalysis, was recently reported and warrants additional attention. …”
Section: Discussionmentioning
confidence: 90%
“…Adsorption transparency, which has implications in catalysis, was recently reported and warrants additional attention. 50…”
Section: Discussionmentioning
confidence: 99%
“…Recently, x-ray techniques including x-ray photoelectron spectroscopy (XPS) and x-ray photon correlation spectroscopy (XPCS) have been utilized to understand how the addition of graphene on an underlying substrate influences adsorption. [18][19][20] Presel et al employed combined experimental XPS and theoretical approach to study adsorption of carbon monoxide (CO) and argon (Ar) and concluded 50% transmission of vdW interactions. 18 In another study, adsorption of water was found to be fully dominated by water-substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Presel et al employed combined experimental XPS and theoretical approach to study adsorption of carbon monoxide (CO) and argon (Ar) and concluded 50% transmission of vdW interactions. 18 In another study, adsorption of water was found to be fully dominated by water-substrate interactions. 19 Additionally, surfacesensitive non-linear spectroscopies, second harmonic generation (SHG) and sum frequency generation (SFG), have been employed to provide insights into graphene's ability to screen or transmit interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report on a successful on-surface metalation of 5,5′-dibromosalophene with Co, Fe, and Cr on Co-intercalated graphene on Ir(111) (Gr/Co) . The graphene layer is known to prevent strong hybridization of molecules with the substrate, , while the intercalation, in the valleys of the moiré pattern, provides sufficient interaction with the molecules to limit the desorption of molecules at elevated temperatures. , The successful realization of the metalation reaction was ensured by X-ray photoelectron spectroscopy (XPS) measurements and by comparison of the electronic structure of ex situ and in situ metalated 5,5′-dibromosalophenato–cobalt­(II). Scanning tunneling spectroscopy (STS) and density functional theory (DFT) calculations of the obtained products reveal the differences in the electronic structures of different metal–organic complexes.…”
Section: Introductionmentioning
confidence: 99%